Family catastrophe - Wang, Wenxing, 1939-; Dolling, Susan Wan, 1950- (Honolulu : University of Hawaii Press, 1995)
A Chinese man walks out of his home in his pajamas and disappears. While searching for him, the son recalls his feelings for his father, a classic case of hero worship in youth followed by disillusion, which the search transforms into regret and understanding.
Part One -- A -- B -- C -- D -- E -- F -- G -- H -- Part Two -- I -- J -- Part Three -- K -- L -- M -- N -- O
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Domestic fiction; Chinese fiction -- 20th century -- Translations into English; Roman familial; FICTION -- Historical; Chinese fiction; Domestic fiction; Chine -- Romans; 1900-1999; "Multi-User"; Domestic fiction; Translations; Historical fiction; Domestic fiction